Analisis Keberterimaan Pengguna terhadap Aplikasi Sistem Manajemen Operasi Irigasi menggunakan Technology Acceptance Model (Studi Kasus Daerah Irigasi Boro, Purworejo) - Marasi Deon Joubert; Aditya Prihantoko (Balai Teknik Irigasi, 2015)
Irrigation Operation Management System (SMOI) is an irrigation operating system developed by the Experimental Station For Irrigation. This system is an irrigation operation application based on website that put forward the concept of the paperless or replace the irrigation operational role in the paper . SMOI technology is designed to be able to process operational data transmission with automatic irrigation network utilizing internet communications services . This SMOI technology testing needs to be done to test trials of the system and the benefits of using this system., The location of the SMOIapplication done in Boro Irrigation Area, Purworedjo District . The methodology used in this study is using the Technology Acceptance Model (TAM) , which is done by taking data about the level of acceptability of the use of the applicationon a population in Boro Irrigation Area, Purworejo by means of questionnaires . Furthermore, the data were statistically analyzed to gain acceptance rate local irrigation management . The analysis showed Ease variable has an influence on the attitude of users SMOI by 78.6 % of respondents answered agree and have a significance level of 0.790, while the benefits of the variables have the support of 82.2% of respondents answered agree and 0.044 significance level. This indicated that the irrigation operation management system(SMOI) of the side benefits to be used more affect than the ease of irrigation management.